The effectiveness of mulligan mobilization with movement (MWM) on outcomes of patients with ankle sprain: a systematic review and meta-analysis - Mohamed M. ElMeligie; Heba A. Abdeen; Hady Atef; Elena Marques-Sule; Rania N. Karkosha (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Ankle sprains are common injuries that cause pain, swelling, and reduced range of motion (ROM), adversely affecting physical activity. In this study, we aim to review the effectiveness of mobilization with movement (MWM) in improving outcomes for patients with ankle sprains. Methods We conducted a search of PubMed, Cochrane Library, PEDro, Web of Science, and Scopus up to October 2023 for English trials comparing Mulligan MWM with other treatments. The Cochrane Risk of Bias tool (ROB 2) was used for quality assessment, and mean differences (MD) with 95% confidence intervals (CI) were calculated. Heterogeneity was evaluated using Cochrane’s Q and I2 statistics. Results A total of 10 trials involving 419 patients (209 in the MWM group and 210 controls) were included. The overall risk of bias was low. MWM significantly reduced pain (MD = - 0.92; 95% CI:[- 1.37, - 0.46]; P < 0.0001) and improved ankle ROM (SMD = 1.65; 95% CI:[0.17, 3.14]; P = 0.03). MWM also demonstrated superior performance in the Star Excursion Balance Test (SEBT) (MD = 3.15; 95% CI:[1.44, 4.86]; P = 0.0003) and Y Balance Test (MD = 4.69; 95% CI:[1.67, 7.70]; P = 0.02). However, no significant differences were found in pain pressure threshold (SMD = - 0.10; 95% CI:[- 0.59, 0.39]; P = 0.7), stiffness perception (MD = 0.10; 95% CI:[- 0.64, 0.85]; P = 0.79), or peroneus longus latency time (MD = - 12.85; 95% CI:[- 22.08, - 3.63]; P = 0.006). The quality evaluation showed that the majority of RCTs revealed some concerns, except of two studies that established a low risk of bias. The GRADE assessment classified the overall evidence as low or very low, due to imprecision, risk of bias, and inconsistency. Conclusions MWM significantly reduced pain and improved ROM and WBLT scores in patients with ankle sprains. The MWM group also showed enhanced balance in the posterolateral SEBT compared to controls.